Examiner performance with visual, probing and FOTI caries diagnosis in the primary dentition - Cleaton-Jones, P.; Daya, N.; Hargreaves, J. A.; et al. (My University, 2001)
To compare clinical reproducibility of dental caries diagnosis in the primary dentition under field conditions, a convenience sample of 5-year-old children in a nursery school in Germiston, was examined for dental caries by four dentists using visual (mirror), visual plus tactile (mirror plus probe) and fibre-optic transillumination (FOTI) methods. Seventeen children were examined on day one and 11 re-examined on day two. Inter-examiner agreement was high, above 90%. Visual examination on its own is comparable with the traditional visual plus tactile method and to FOTI under field conditions. New caries data collected by visual diagnosis alone may, reasonably, be compared with historical data diagnosed with visual + tactile examination.
PK
Keywords: Dental Caries/diagnosis; Diagnosis, Oral; Tooth, Deciduous